2013
DOI: 10.1183/09031936.00055213
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of relapse after discontinuation of infliximab therapy in severe sarcoidosis

Abstract: Infliximab is effective as a third-line therapeutic for severe sarcoidosis; however, long-term efficacy is unknown. The aim of this study was to assess the relapse rate after discontinuation of infliximab in sarcoidosis patients and predict relapse by analysis of the activity marker soluble interleukin (IL)-2 receptor (sIL-2R) and maximum standardised uptake value (SUVmax) of 18 F-fluorodeoxyglucose positron emission tomography (FDG PET).In this retrospective cohort study, the proportion of relapse was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 25 publications
2
63
0
1
Order By: Relevance
“…sIL-2R was previously shown to correlate with the amount of CD4 + T-lymphocytes in bronchoalveolar lavage fluid [3]. Furthermore, it was shown that sIL-2R >4000 pg·mL −1 was a significant predictor of relapse after discontinuation of infliximab therapy and that sIL-2R is a suitable prognostic marker for disease progression [4,5]. We observed, however, that in a small number of patients with co-existing renal insufficiency, sIL-2R can be disproportionately high without marked signs of disease activity based on 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET), ACE and the clinical presentation.…”
Section: Discrepant Elevation Of Sil-2r Levels In Sarcoidosis Patientmentioning
confidence: 96%
“…sIL-2R was previously shown to correlate with the amount of CD4 + T-lymphocytes in bronchoalveolar lavage fluid [3]. Furthermore, it was shown that sIL-2R >4000 pg·mL −1 was a significant predictor of relapse after discontinuation of infliximab therapy and that sIL-2R is a suitable prognostic marker for disease progression [4,5]. We observed, however, that in a small number of patients with co-existing renal insufficiency, sIL-2R can be disproportionately high without marked signs of disease activity based on 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET), ACE and the clinical presentation.…”
Section: Discrepant Elevation Of Sil-2r Levels In Sarcoidosis Patientmentioning
confidence: 96%
“…Patients with high activity on 18 F-fluorodeoxyglucose (FDG) by positron emission tomography (PET) were often shown to relapse after infliximab therapy was discontinued [23], possibly suggesting a good initial response in those patients.…”
Section: Introductionmentioning
confidence: 99%
“…In case of intolerable side-effects or steroid resistance, second-line treatment options should be considered, such as methotrexate (MTX), azathioprine or leflunomide, but these therapies may also be subject to failure or intolerance [8][9][10]. Another option to consider is TNF inhibitors, which inhibit the potent pro-inflammatory TNF-a, often a predominant problem in patients with refractory sarcoidosis, and these have shown promising results [11][12][13][14]. However, a drawback of TNF inhibitors is considerable treatment costs [15].…”
Section: Introductionmentioning
confidence: 99%